Impacto da prematuridade sobre os critérios de diagnóstico da síndrome metabólica em adolescentes - Toso, Fabíula dos Santos (2020)
Prematurity is the main cause of infant mortality and the leading cause of hospitalization in neonatal intensive care units worldwide. Prematurity rates have increased over the years, but thanks to technological development, better training of professionals and family involvement, morbidity and mortality has been reduced. Consequently, there was an increase in the survival of these children, which has several repercussions that can be observed in all age groups throughout life. Among the late complications, there are differentiated growth, hormonal and metabolic alterations, which lead individuals to higher rates of overweight, obesity, type 2 diabetes mellitus, coronary artery disease and arterial hypertension. Associating these changes with increased sedentary lifestyle in modern life, metabolic syndrome is increasingly evident among adolescents and its incidence has increased every year. Thus, the present study aims to present the anthropometric, pressure, glycemic and lipid profile of full-term adolescents, comparing them to the similar cohort of preterm born adolescents, both living in the western region of the municipality of Cascavel, Paraná. The study is cross-sectional, with a convenience sample composed of 150 adolescents from 10 to 19 years of age, born at term and 50 adolescents born preterm. Interviews and physical evaluation were conducted, with blood pressure measurement, anthropometric measurement, abdominal circumference and blood collection by capillary puncture for glucose, total cholesterol and triglycerides tests. The results showed that the majority, in both groups, are composed of eutrophic individuals, however, 34% of the term and 30% of the preterms were overweight or obese. There was no statistically significant difference between the sociodemographic, anthropometric, pressure and glycemic profiles between the groups. The highest means were found in the percentile variables of abdominal circumference, mean systolic blood pressure, glycemia and triglycerides of the subjects of the group of full-term adolescents (p<0.05). The prevalence of metabolic syndrome was 12% among full-term adolescents and only 10 2% among preterm infants (x2=4.36; p=0.037). Thus, it can be inferred that, although prematurity is considered a risk factor for chronic diseases, life habits can constitute an aggravating factor for full-term individuals, overlapping prematurity. Actions and interventions to promote health and prevent injuries should be planned by adolescent follow-up services in primary care, regardless of their gestational age, in order to reduce excess weight and, consequently, metabolic alterations that may put them at risk of developing health complications, such as cardiovascular diseases.